Перспективи і тенденції інвестиційної діяльності страхових компаній в Україні - Павленко, Оксана Павлівна; Pavlenko, Oksana (Видавнича група «Наукові перспективи», 2023)
Світові тенденції розвитку вказують на інтенсивний курс стабілізації економіки України. Тому реформування фінансової системи та покращення основних інвестиційних показників його діяльності насамперед необхідно з відновлення страхового сектору. В статті автором розглянуто системи внутрішнього контролю страховиків, контролю за дотриманням норм щодо розмірів активів, страхових резервів, капіталу страховиків, комплаєнсконтролю, застосуванню внутрішнього аудиту відповідно до Міжнародних стандартів професійної практики внутрішнього аудиту, проведення правильності актуарних розрахунків, а також згідно з чинними нормами страхового законодавства втілення у страхову практику аутсорсингу. Проведено аналіз ризикованих страховиків за розмірами гарантійного фонду, страховими платежами та відшкодуваннями. Визначено структуру капітальних активів за видами економічної діяльності, насамперед фінансової, страхової і перестрахової діяльності, сфери обов’язкового соціального страхування, допоміжної діяльності у страхуванні. Проведені дослідження показали, шо інвестування фінансових інструментів страховиків в матеріальні активи займають найбільшу частку. Страхові компанії здійснюють інвестування капіталу в доходні фінансові інструменти та інші активи, що сприяє підвищенню фінансової стійкості та диверсифікації структури страхового і інвестиційного портфеля, управлінню ліквідності та впровадженню високо інтегрованих технологій на фондовому ринку. Визначені стратегічні підходи страховиків-інвесторів до масштабних відрахувань у ризикові активи, які водночас мають більший рівень доходності. Trends of world development indicate to an intensive course of stabilization of Ukraine's economy. Therefore, reforming the financial system and improving the main investment indicators of its activity are primarily necessary for the recovery of the insurance sector. The internal control systems of insurers, control over compliance with the norms regarding the size of assets, insurance reserves, insurers' capital, compliance control, the application of internal audit in accordance with the International Standards of Professional Practice of Internal Audit, the correctness of actuarial calculations, as well as, in accordance with the current norms of insurance legislation, the implementation of outsourcing in the insurance practice were considered in the article. An analysis of risky insurers was carried out according to the size of the guarantee fund, insurance payments and reimbursements. The structure of capital assets by types of economic activity, primarily financial, insurance and reinsurance activities, the field of mandatory social insurance, auxiliary activities in insurance is determined. The conducted studies showed that the investment of insurers' financial instruments in tangible assets occupies the largest share. The conducted studies showed that the investment of insurers' financial instruments in tangible assets occupies the largest share. Insurance companies invest capital in profitable financial instruments and other assets, which contributes to increasing financial stability and diversification of the structure of the insurance and investment portfolio, liquidity management and implementation of highly integrated technologies on the stock market. The strategic approaches of investor-insurers to large-scale deductions in risky assets, that have a higher level of profitability and liquidity, are able to overcome crisis phenomena, stable growth of inflation, a new regime of increased market macroeconomic volatility. So, for insurance investors, intangible assets, digital technologies, fund assets, and risky financial instruments have the tendency to be more attractive. Therefore, the goals of the investment and innovation activities of insurers are becoming more dynamic than the search for a profitable result or increasing diversification.
Prospects and trends of investment activities of insurance companies of Ukraine
Keywords: страхування; insurance; страховий ринок; insurance market; страховик; insurer; страхова компанія; insurance company; страхова організація; insurance organization; страхові премії; insurance premiums; страхові виплати; insurance payments; інвестиції страховиків; insurers' investments; активи страховиків; insurers' assets; інвестування; investment; ліквідність; liquidity